2022
DOI: 10.1021/acs.est.2c06942
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Driven Production of Reactive Oxygen Species from Natural Iron Minerals: Quantum Yield and Wavelength Dependence

Abstract: Photochemically generated reactive oxygen species (ROS) play numerous key roles in earth's surface biogeochemical processes and pollutant dynamics. ROS production has historically been linked to the photosensitization of natural organic matter. Here, we report the photochemical ROS production from three naturally abundant iron minerals. All investigated iron minerals are photoactive toward sunlight irradiation, with photogenerated currents linearly correlated with incident light intensity. Hydroxyl radicals ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…The findings of spontaneous production of • OH through water vapor condensation on iron minerals expand the natural source and spatial-temporal distribution of • OH. Our recent study revealed that under sunlight irradiation iron minerals can photochemically produce • OH (Figure ) with apparent quantum yield from 1.4 × 10 –8 to 3.9 × 10 –8 . As a supplement to the photochemical • OH in the daytime, water vapor condensation and • OH production on iron minerals could occur in the nighttime when temperature drops below the dew point (Figure ).…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of spontaneous production of • OH through water vapor condensation on iron minerals expand the natural source and spatial-temporal distribution of • OH. Our recent study revealed that under sunlight irradiation iron minerals can photochemically produce • OH (Figure ) with apparent quantum yield from 1.4 × 10 –8 to 3.9 × 10 –8 . As a supplement to the photochemical • OH in the daytime, water vapor condensation and • OH production on iron minerals could occur in the nighttime when temperature drops below the dew point (Figure ).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Our recent study revealed that under sunlight irradiation iron minerals can photochemically produce • OH (Figure 5) with apparent quantum yield from 1.4 × 10 −8 to 3.9 × 10 −8 . 42 As a supplement to the photochemical • OH in the daytime, water vapor condensation and • OH production on iron minerals could occur in the nighttime when temperature drops below the dew point (Figure 5). We expect this process to ubiquitously occur on iron minerals in the desert as well as in subsurface soils of arid/semiarid areas with high air permeability.…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%
“…3 In addition to adsorption, the iron minerals are able to produce hydroxyl radicals (•OH) with light irradiation to induce the oxidative transformation of pollutants. 7 The production of •OH by iron minerals is generally thought to be limited to environments with access to light. 7,8 Nevertheless, recent reports have shown that iron minerals are capable of reducing oxygen to produce •OH under dark conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have a pervasive presence in nature and play pivotal roles in regulating environmental processes . Traditionally, ROS productions have been attributed to photochemistry involving organic photosensitizers (such as natural organic matter and black carbon) and inorganic compounds (such as nitrate and iron minerals). Recent advances have shed light on non-photochemical ROS production through electron transfer from reduced substances [such as reduced natural organic matter (NOM) and iron minerals] to molecular oxygen (O 2 ). , One prominent example is pyrite, the most prevalent naturally occurring ferrous sulfide mineral widely distributed in nature, with 0.5–5% typical content in modern sediments, which undergoes oxidation in regions characterized by frequent hydrological purtabations and redox oscillations (e.g., wetland, rice paddy, coast, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have a pervasive presence in nature and play pivotal roles in regulating environmental processes. 1 Traditionally, ROS productions have been attributed to photochemistry involving organic photosensitizers (such as natural organic matter 2 and black carbon 3 ) and inorganic compounds (such as nitrate 4 and iron minerals 5 ). Recent advances have shed light on non-photochemical ROS production through electron transfer from reduced substances [such as reduced natural organic matter (NOM) and iron minerals] to molecular oxygen (O 2 ).…”
Section: ■ Introductionmentioning
confidence: 99%